Screening of CD96 and ASXL1 in 11 patients with Opitz C or Bohring–Opitz syndromes. Issue 1 (7th October 2015) - Urreizti, Roser; Roca‐Ayats, Neus; Trepat, Judith; Garcia‐Garcia, Francisco; Aleman, Alejandro; Orteschi, Daniela; Marangi, Giuseppe; Neri, Giovanni; Opitz, John M.; Dopazo, Joaquin; Cormand, Bru; Vilageliu, Lluïsa; et al.
Abstract : Opitz C trigonocephaly (or Opitz C syndrome, OTCS) and Bohring‐Opitz syndrome (BOS or C‐like syndrome) are two rare genetic disorders with phenotypic overlap. The genetic causes of these diseases are not understood. However, two genes have been associated with OTCS or BOS with dominantly inherited de novo mutations. Whereas CD96 has been related to OTCS (one case) and to BOS (one case), ASXL1 has been related to BOS only (several cases). In this study we analyze CD96 and ASXL1 in a group of 11 affected individuals, including 2 sibs, 10 of them were diagnosed with OTCS, and one had a BOS phenotype. Exome sequences were available on six patients with OTCS and three parent pairs. Thus, we could analyze the CD96 and ASXL1 sequences in these patients bioinformatically. Sanger sequencing of all exons of CD96 and ASXL1 was carried out in the remaining patients. Detailed scrutiny of the sequences and assessment of variants allowed us to exclude putative pathogenic and private mutations in all but one of the patients. In this patient (with BOS) we identified a de novo mutation in ASXL1 (c.2100dupT). By nature and location within the gene, this mutation resembles those previously described in other BOS patients and we conclude that it may be responsible for the condition. Our results indicate that in 10 of 11, the disease (OTCS or BOS) cannot be explained by small changes in CD96 or ASXL1 . However, the cohort is too small to make generalizations about the genetic etiology of these diseases. © 2015 Wiley Periodicals, Inc.